PRESIDENTIAL SYSTEM POST CONSOLIDATION ELECTION 2019: MEASUREMENT OF THE THRESHOLD STRENGTH OF PRESIDENTIAL CANDIDATES - Mhd Ansor Lubis (NOMOI Law Review, 2022)
The implementation of the General Election for President and Vice President in its development has not been able to become a means of transforming social change in the desired direction and does not significantly prove the influence of simultaneous elections on governance in the President's power. The Nomination Threshold in the Design of the Election Law actually creates a coalition of parties that has the potential to damage a healthy and accountable political system, namely the gathering of parties in one support for a presidential candidate which is then not matched by the existence of an opposition within the Check and Balance framework. The research method used in this paper is a normative juridical research method. Normative research with a statutory approach and a conceptual approach. The results of the study obtained include, strengthening the presidential system through the presidential candidate threshold after the election consolidation is less effective and tends to eliminate the rights of citizens to be able to vote, nominate themselves and nominate candidates.